Romantic Revelations : - Washington, Chris (University of Toronto Press, 2019)
Romantic Revelations shows that the nonhuman is fundamental to Romanticism’s political responses to climatic catastrophes. Exploring what he calls
10.3138/9781487530310
Keywords: Apocalyptic literature; End of the world in literature.; English literature; Romanticism; Anthropocene.; Frankenstein.; Jane Austen.; Lord Byron.; Mary Shelley.; Percy Shelley.; Romanticism.; apocalypse.; climate change.; environmental history.; history of literature.; literary criticism.; post-apocalyptic Romanticism.; post-apocalyptic literature.; LITERARY CRITICISM / Modern / 18th Century .